XDR and MDR tuberculosis from a tertiary chest hospital in Bangladesh (Bangladesh Journal of Medical Microbiology, 2013)
The present article provides an overview of the new diagnostic options available for diagnosis of drug resistant tuberculosis, which include liquid based culture and susceptibility tests. To effectively address the threats of drug resistant tuberculosis, global initiatives are required to scale-up culture and drug susceptibility testing capacities. In parallel efforts are needed to expand the use of new technologies for rapid diagnosis of drug resistance.The study was carried out at National Institute of Diseases of Chest and Hospital (NIDCH), Mohakhali, Dhaka, which is the only tertiary- level chest disease hospital for the treatment of referred patients from all over the country. One morning sputum sample was taken from each of the 50 suspected new pulmonary tuberculosis patients and 50 samples from previously treated group included patients who did not complete the full regimen or those who did not respond to antibiotic treatment. All samples were cultured on sula liquid media for 12 days. Sensitivity tests against isoniazid (INH), rifampicin (RMP), streptomycin (SM) and ethambutol (EMB), gatifloxacin (G),kanamycin (K) and ofloxacin (OF) were done by slide culture  method. Sensitivity test against P-nitro benzoic acid (PNB) were also done to differentiate typical Mycobacterium from atypical Mycobacterium.Among the 50 isolated new cases 98% were sensitive to isoniazid, rifampicin and streptomycin. Regarding resistant pattern for MDR-TB to second line drugs, 2% were resistant to kanamycin and 10% to ofloxacin.One MDR-TB which was resistant to kanamycin was also resistant to ofloxacin. Hence it was identified as extensively-drug resistant tuberculosis (XDR-TB).No atypical Mycobacteria were detected by PNB.DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19329 Bangladesh J Med Microbiol 2013; 07(02): 17-20